On Some Ambiguities of the Absorption Edge and Optical Band Gaps of Amorphous and Polycrystalline Semiconductors - Mullerova, Jarmila; Sutta, Pavol (Communications - Scientific letters of the University of Zilina, 2017)
This paper reports on somewhat puzzling character of the determination of the optical band gap energies of amorphous and polycrystalline semiconductors, where probably the mixed-phase composition and structural and compositional disorder are main reasons for the ambiguities. The analysis is performed using spectra of absorption coefficients of the featured samples of Si:H and Zn-Ti-O extracted by numerical analysis of transmittance measurements. The differences originating from using several procedures to process spectra of absorption coefficients are discussed.